The Parental Co-Immunization Hypothesis - Miguel Portela; Paul Schweinzer (Center for Economic Studies and ifo Institute (CESifo), 2013)
We attempt to answer a simple empirical question: does having children make a parent live longer? The hypothesis we offer is that a parent's immune system is refreshed by a child's infections at a time when their own protection starts wearing thin. With the boosted immune system, the parent has a better chance to fend off whatever infections might strike when old and weak. Thus, parenthood is rewarded in individual terms. Using the Office for National Statistics Longitudinal Study (ONS-LS) data set following one percent of the population of England and Wales along four census waves 1971, 1981, 1991, and 2001, we are unable to reject this hypothesis. By contrast, we find in our key result that women with children have a roughly 8% higher survival probability than women without children.
Keywords: J10; 330; longevity; infectious diseases; family